The Influence of Environmental Accounting on Sustainability Development with Return on Asset as a Moderating Variable - Fari'ah, Hesti; Sutihat, Eva; Permatasari, Novelia Kiki (International Conference on Business Management and Accounting, 2023)
The purpose of this study is to provide strong evidence regarding the effect of environmental accounting on sustainability development with Return on Assets as a moderating variable in mining companies listed on the IDX. Environmental Accounting in research is measured by PROPER. Sustainability Development is measured by SRDI. The company's Return on Assets is measured by ROA. This type of research includes quantitative research. The population in this study are mining companies that have won the PROPER award and have published sustainability reports for 2021-2022. Meanwhile, the sample in the research used purposing sampling, and 25 companies were obtained from members of the population. The data collection technique is documentation techniques. The data management technique of this research uses Microsoft Excel and Eviews 9 applications. The analysis used in this study is regression analysis with moderating variables (MRA). The results in this study prove that environmental accounting has a significant effect on sustainability development, the interaction variable between environmental accounting and corporate ROA has no significant effect on sustainability development, corporate ROA is not classified as a moderating variable thereby weakening the effect of environmental accounting on sustainability development.